Unionization of retired workers in Europe - Vinzenz Pyka; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2023)
We shed light on an understudied group: retirees in unions. Using representative individual-level data of 19 European countries, we find that the share of retirees in unions and the union density of retirees increased between 2008 and 2020. Econometric analyses indicate that on average retired workers' probability of union membership is 17 percentage points lower than that of active workers. This finding is consistent with social custom models and cost-benefit considerations. We further find that some determinants of union membership differ between active and retired workers and that standard membership models better explain the unionization of active than retired workers. – – Wir untersuchen eine untererforschte Gruppe: Rentner in Gewerkschaften. Basierend auf repräsentativen Individualdaten für 19 europäische Länder finden wir, dass der Rentneranteil in Gewerkschaften und der gewerkschaftliche Organisationsgrad von Rentnern zwischen 2008 und 2020 gestiegen sind. Ökonometrische Analysen zeigen, dass die Wahrscheinlichkeit einer gewerkschaftlichen Mitgliedschaft für Rentner im Durchschnitt 17 Prozentpunkte geringer ausfällt als für Beschäftigte. Diese Erkenntnis ist vereinbar mit "social custom"-Modellen und Kosten-Nutzen-Überlegungen. Wir finden zudem, dass sich einige Determinanten der gewerkschaftlichen Mitgliedschaft zwischen aktiven und verrenteten Arbeitskräften unterscheiden und dass die üblichen Mitgliedschaftsmodelle besser die gewerkschaftliche Organisierung von aktiven als von verrenteten Arbeitskräften erklären können.
Keywords: J26; J51; 330; trade union; retirement; union membership; Europe